2017
DOI: 10.1038/srep40763
|View full text |Cite|
|
Sign up to set email alerts
|

Optical coherence tomography angiography microvascular findings in macular edema due to central and branch retinal vein occlusions

Abstract: The aim of this study was to evaluate retinal and choriocapillaris vessel density using optical coherence tomography angiography (OCTA) in eyes with central retinal vein occlusion (CRVO) and branch retinal vein occlusion (BRVO) complicated by macular edema (ME). Sixty eyes of 60 patients with CRVO or BRVO and ME and 40 healthy subjects underwent measurements of superficial and deep foveal and parafoveal vessel density (FVD, PFVD) and choricapillary density using OCTA at baseline and 60 days after intravitreal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 30 publications
4
53
3
1
Order By: Relevance
“…For example, SSI ≥40 was used as the cut‐off threshold in the Tang et al study for evaluation of quantitative metrics in diabetic patients and the Cao et al study evaluating patients with preclinical DR. SSI ≥50 was applied in the studies reported by Samara et al, Wang et al and Seknazi et al for quantitative analysis and in the study by Iida et al for qualitative assessment of OCTA features in patients with RVO. This threshold was also used in the Hwang et al study for quantification of capillary non‐perfusion in DR. A higher threshold of SSI ≥60 was used by other studies, such as Mastropasqua et al to analyse VR in patients with RVO complicated with macular oedema, and Golebiewska et al to assess OCTA features in children with type 1 DM. Conversely, in more recent studies using Optovue device, an SQI of ≥6 was used as the threshold for acceptable images .…”
Section: Discussionmentioning
confidence: 99%
“…For example, SSI ≥40 was used as the cut‐off threshold in the Tang et al study for evaluation of quantitative metrics in diabetic patients and the Cao et al study evaluating patients with preclinical DR. SSI ≥50 was applied in the studies reported by Samara et al, Wang et al and Seknazi et al for quantitative analysis and in the study by Iida et al for qualitative assessment of OCTA features in patients with RVO. This threshold was also used in the Hwang et al study for quantification of capillary non‐perfusion in DR. A higher threshold of SSI ≥60 was used by other studies, such as Mastropasqua et al to analyse VR in patients with RVO complicated with macular oedema, and Golebiewska et al to assess OCTA features in children with type 1 DM. Conversely, in more recent studies using Optovue device, an SQI of ≥6 was used as the threshold for acceptable images .…”
Section: Discussionmentioning
confidence: 99%
“… Non-perfusion areas (NPAs ; Figures 1 to 4 ):[ 32 ] These are also called grayish areas[ 39 ] and areas with decreased vascular perfusion. [ 6 40 ] These areas are regions without visible perfused capillaries. In RVOs, they are more extensive in the DCP than in the SCP.…”
Section: A Brief Discussion About Octamentioning
confidence: 99%
“…In RVOs, they are more extensive in the DCP than in the SCP. [ 6 10 32 33 39 40 ] These areas are more readily visible with OCTA than with FA. [ 12 ] There may be a decrease in the vascular perfusion in both the SCP and DCP of the fellow eye of RVO patients relative to normal controls, which may be a sign of previous silent RVOs in these eyes.…”
Section: A Brief Discussion About Octamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous papers revealed a reduction of foveal and parafoveal retinal superficial and deep vascular density and choriocapillaris density in eyes with vein occlusion-related ME [ 33 35 ]. Although Mastropasqua et al found that retinal vessel plexi density did not change significantly after DEX implant and there was no correlation between vessel density and functional parameters such as visual acuity and retinal sensitivity [ 36 ], it has been demonstrated that intravitreal steroid, in eyes with macular edema due to retinal vein occlusion or diabetic retinopathy, causes a reduction of vessel diameter probably due to the blockage of VEGF [ 37 , 38 ]. Vessel occlusion may lead to functional damage of photoreceptor cells that influence visual acuity and retinal sensitivity.…”
Section: Discussionmentioning
confidence: 99%